A Theory Book of Herbal Drug Technology - Ms. Neelima Yadav; Dr. Saket Singh Chandel; Dr. T. Venkatachalam; Dr. Roopam Devaliya; Dr. Shivani Vaidya (A Theory Book of Herbal Drug Technology, Edition 1, 2024)
The uses of herbal medications are the main topic of this book, which serves as a thorough reference for B. Pharm sixth semester students. Along with their source and quality control, it addresses the fundamentals of employing herbs as raw materials. The focus is on sustainable farming methods and biodynamic agriculture. Ayurveda, Unani, and Siddha are just a few of the Indian medical systems highlighted in this literature. It covers the investigation into particular herbs as health foods and the advantages of nutraceuticals for health. The book talks about herbal-drug and herb-food interactions that raise safety issues. It describes the application and function of herbal excipients and cosmetics in relation to product stability. There is also a full explanation of the steps involved in creating herbal formulations and how to assess the quality of drugs. Along with a broad overview of the herbal industry, the book offers insights into regulatory requirements for natural products and patenting. It also covers Schedule T, which describes excellent manufacturing procedures for Indian medical systems. Students who purchase this textbook will gain the fundamental knowledge and abilities needed for a career in the herbal medication sector.